2000
DOI: 10.1302/0301-620x.82b6.0820795
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of thromboembolic prophylaxis after total knee arthroplasty

Abstract: We performed a meta-analysis of the English literature to assess the efficacy of four common regimes for thromboembolic prophylaxis after total knee arthroplasty: aspirin, warfarin, low-molecular-weight heparin (LMWH) and pneumatic compression. We reviewed 136 articles and abstracts published between January 1980 and December 1997. Papers not using routine venography and a lung scan or angiography to detect deep-venous thrombosis (DVT) and pulmonary emboli (PE) respectively, were excluded. Of the 136 studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 35 publications
(88 reference statements)
1
38
1
1
Order By: Relevance
“…First, we only included head-to-head randomized trials such that all included data reflect direct comparisons between aspirin and anticoagulation in well-balanced populations. Conversely, both recent reviews 11,12 were based on indirect comparisons, a type of analysis in which data for the intervention and control arms are taken from different studies and thus different populations. This methodology is not recommended by the Cochrane Collaboration 13,14 because of the increased risk of an unbalanced comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we only included head-to-head randomized trials such that all included data reflect direct comparisons between aspirin and anticoagulation in well-balanced populations. Conversely, both recent reviews 11,12 were based on indirect comparisons, a type of analysis in which data for the intervention and control arms are taken from different studies and thus different populations. This methodology is not recommended by the Cochrane Collaboration 13,14 because of the increased risk of an unbalanced comparison.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,10 Two previous systematic reviews comparing aspirin to anticoagulation for VTE prevention found conflicting results. 11,12 In addition, both used indirect comparisons, a method in which the intervention and comparison data come from different studies, and susceptibility to confounding is high. 13,14 We aimed to overcome the limitations of prior efforts to address this commonly encountered clinical question by conducting a systematic review and meta-analysis of randomized controlled trials that directly compared the efficacy and safety of aspirin to anticoagulants for VTE prevention in adults undergoing common highrisk major orthopedic surgeries of the lower extremities.…”
Section: Society Of Hospital Medicinementioning
confidence: 99%
“…There is abundant evidence examining the efficacy for the prevention of asymptomatic deep venous thrombosis. 11 reports similar results, but notably also a dramatic risk reduction in patients treated by a post-operative compression device. Multimodal therapy and the use of intermittent mechanical compression devices have been sparsely reviewed by the literature; two recent reviews summarize the data on intermittent compression devices with results comparable or superior to chemoprophylaxis.…”
Section: Venous Thromboembolic Prophylaxismentioning
confidence: 53%
“…35 Intermittent pneumatic calf compression is also an effective means of VTE prophylaxis. 36,37 Warwick et al reported a randomized study between foot pumps and enoxaparin that showed similar VTE prophylaxis. 38 The use of thromboprophylaxis has measurably reduced the incidence of DVT and non-fatal PE but not the rate of fatal PE or all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%